Association of Coxsackievirus infection with serum Interleukin-12 levels in Iraqi patients with Dilated Cardiomyopathy - Adel Najah (22619843) (2025)
This study investigates the relationship between dilated cardiomyopathy (DCM) and factors such as lipid levels, interleukin-12 (IL-12) levels, troponin levels, and coxsackievirus antibodies. The study involved 60 patients diagnosed with DCM and 30 healthy controls. Lipid profiles were measured using a BioSystems kit, and troponin levels were quantified using a fully automated c111 analyzer (Germany). IL-12 levels and antibodies (IgG and IgM) to coxsackievirus were evaluated using ELISA. Data were analyzed using SPSS, with statistically significant defined as p ≤ 0.05.The results revealed a significant difference in lipid levels between DCM patients and the control group, with HDL levels showing no statistically significant difference. Troponin levels were significantly higher in DCM patients. IL-12 levels were elevated by 1.27-fold in DCM patients, suggesting diagnostic accuracy. The levels of antibodies against coxsackievirus (IgG and IgM) were significantly higher in DCM patients, with positive tests for both IgG and IgM, while no positive results were observed in the control group. However, no significant correlation was found between IL-12 levels and coxsackievirus antibodies